Reading Arrazy Hasyim's Oral Exegesis of The Law of Greetings Merry Christmas on Social Media - Ahmad Murtaza MZ; Efridayanti Nasution (An-Nisa' Journal of Gender Studies, 2022)
This article looks at the oral interpretation of the law of saying Christmas delivered by Arrazy Hasyim in the Close The Door podcast owned by Deddy Corbuzier. This study uses qualitative methods, so the data collection used by researchers is the method of observation, interviews, and documentation. This article uses an oral interpretation analysis initiated by Andreas Goerke. According to Goerke, the interpretation literature is experiencing dynamics that bring significant changes where all interpretations can be accessed easily both in hard and soft files, even online on social media. To see the form of Arrzy's oral interpretation, first, describe Arrazy Hasyim's view on the law of saying Christmas. Then this view is analyzed interpretively by comparing the opinions of other scholars. This study concludes that Arrazy Hasim regarding the law of saying Merry Christmas is permissible for Christians because it does not reduce the value of the 'aqeedah of someone who says it. And his views are so relevant in the Indonesian context today.